2019
DOI: 10.1016/s1470-2045(19)30161-5
|View full text |Cite|
|
Sign up to set email alerts
|

Two-view digital breast tomosynthesis versus digital mammography in a population-based breast cancer screening programme (To-Be): a randomised, controlled trial

Abstract: Two-view digital breast tomosynthesis versus digital mammography in a population-based breast cancer screening program (To-Be): a randomized, controlled trialTomosynthesis breast in screeninga randomized controlled trial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 28 publications
2
70
2
4
Order By: Relevance
“…After completely reading these references, 18 studies (comprising 26 articles, since some had more than one published article) met our eligibility criteria and therefore were included in this review [4][5][6][7][8][24][25][26][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After completely reading these references, 18 studies (comprising 26 articles, since some had more than one published article) met our eligibility criteria and therefore were included in this review [4][5][6][7][8][24][25][26][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] .…”
Section: Resultsmentioning
confidence: 99%
“…These studies included: one RCT 24 , five accuracy studies 7,34,35,40,44 , and eight retrospective cohort studies [4][5][6]8,[36][37][38]46 . Six studies, three accuracy studies 35,43,48 , one prospective cohort study 47 , one RCT 25 and one quasi-RCT 26 evaluated the effectiveness of DBT with synthetic mammography versus digital mammography alone.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding specificity, there is no consensus on whether DBT specificity is improved compared to DM. Some studies showed that specificity can be improved with adjunct DBT compared to DM alone [43,44]. However, a meta-analysis addressed that the recall rate of adjunct DBT increased slightly in European countries, where the recall rate of DM was relatively low compared to other regions such as the USA [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, supplementary ultrasounds also increase the rate of recall for further testing (e.g., biopsy) for women who do not have breast cancer, known as a "false positive" [20]. Tomosynthesis (also known as three-dimensional mammography) is a screening modality that increases cancer detection compared to mammography, including in women with dense breasts [21]; however, no randomised-controlled trials have been conducted long enough to investigate improvements in interval cancer-detection rates or survival rates [22]. A randomised-controlled trial demonstrated diagnosis of significantly fewer interval cancers when adjunct magnetic resonance imaging was used for women with extremely dense breasts compared to mammography alone during a 2-year screening period [23].…”
Section: Uncertainties In Measurement and Management Pathwaysmentioning
confidence: 99%